(untitled) (Geo-Eco-Marina, 2013)
Natural diversity, in its inner structure, has two major components: biological diversity (biodiversity) and geological diversity (geodiversity). However, while the former has already gained a clear status, being used and accepted worldwide, we cannot say the same about the latter, the geodiversity. This paper tries to highlight the defining elements, values, vulnerabilities and threats to geodiversity applied to five geological reserves from Dobrogea, by referring to the legislation, using existing scientific and public information and discussing the utility of such an initiative, aiming to contribute to the protection and conservation of the geological heritage in Romania.